Tata Ruang Rumah Ideal dalam Novel Teka-Teki Rumah Aneh Karya Uketsu - Ifroh Ya Albi; Muhammad Raaid Hammas El Ghazali; Eva Dwi Kurniawan (Sustainable Civil Building Management and Engineering Journal, 2024)
Houses, serving as spaces for human interaction and socialization, require meticulous design to create environments that provide protection and comfort. This research focuses on spatial layout within homes as a critical factor influencing functionality, aesthetics, and inhabitant health, referencing Uketsu's novel "Teka-Teki Rumah Aneh." Employing hermeneutics and semiotics as text analysis methods, the study aims to unveil hidden meanings. Hermeneutics utilizes three main approaches, while semiotics concentrates on signs within objects, enabling a holistic and in-depth understanding of the text's context. The research emphasizes the division of spatial characteristics and efficiency in room utilization, indicating that building layouts may not entirely align with ideal spatial concepts. The significance of efficient placement of walls and doors, along with the integration of elements such as windows, is highlighted to create floor plans more in line with the ideal spatial concepts for homes. The research findings assert that the arrangement of living spaces should ideally blend practical functionality with appealing aesthetics, giving top priority to the comfort and health of the inhabitants.